URGENSI PENGATURAN PENGEMBANGAN ENERGI TERBARUKAN SEBAGAI WUJUD MENDUKUNG KETAHANAN ENERGI NASIONAL - Faisal, Faisal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Energy sovereignty in Indonesia is experiencing problems with a decline in national energy security. Indonesia's energy system is currently facing serious challenges. The imbalance in the condition of energy supplies with national energy needs, especially the oil and gas sector and efforts to fulfill national energy needs in a sustainable manner are the main problems of this nation in the energy sector. It is absolutely necessary to have strategic efforts in the field of creating new and renewable energy. Although the government has issued various policies to catch up, but to realize national energy security, it is necessary to urgently regulate the development of renewable energy as a form of supporting national energy security. As for the formulation of the problems raised in this study are: support national energy security in Indonesia? 2) what is the urgency of regulating the development of renewable energy as a form of supporting national energy security? This research will use normative juridical research and supported by empirical juridical research so that it will be able to see the conditions of developing renewable energy as a form of supporting national energy security in Indonesia. To realize this, it is necessary to urgently regulate the development of renewable energy as a form of supporting national energy security.